The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4007/annals.2011.173.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Hausdorff dimension of the set of singular pairs

Abstract: In this paper we show that the Hausdorff dimension of the set of singular pairs is . We also show that the action of diag(e t , e t , e −2t ) on SL3R/SL3Z admits divergent trajectories that exit to infinity at arbitrarily slow prescribed rates, answering a question of A. N. Starkov. As a by-product of the analysis, we obtain a higher-dimensional generalization of the basic inequalities satisfied by convergents of continued fractions. As an illustration of the technique used to compute Hausdorff dimension, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 28 publications
2
96
0
1
Order By: Relevance
“…In a remarkable article, the Hausdorff dimension of Sing(2) was determined by Cheung [Che11]. This result was extended by Cheung and Chevallier in [CC16] to higher dimensions.…”
Section: Introductionmentioning
confidence: 91%
“…In a remarkable article, the Hausdorff dimension of Sing(2) was determined by Cheung [Che11]. This result was extended by Cheung and Chevallier in [CC16] to higher dimensions.…”
Section: Introductionmentioning
confidence: 91%
“…When the quadric X has Q-rank at least 2, it is natural to expect that there exist some nontrivial singular points. It might then be interesting to compute the Hausdorff dimension of the set of singular points on X, similarly to what has been done in [7,8] for Diophantine approximation in the Euclidean space.…”
Section: Further Directions and Open Problemsmentioning
confidence: 99%
“…Davenport and Schmidt in the 1970s showed that Sing (d) is a set of d‐dimensional Lebesgue measure zero. Recently, Cheung and Chevallier , building on the spectacular d=2 work of Cheung , have shown that Sing (d) has Hausdorff dimensiond2/false(d+1false).…”
Section: The General Setup and Main Problemsmentioning
confidence: 99%
“…It is not difficult to see that the set Sing(d) of singular vectors contains every rational hyperplane in R d and thus its Hausdorff dimension is between d − 1 and d. In the case d = 1, a nifty argument (which we will utilise) due to Khintchine [24] shows that a real number is singular if and only if it is rational; that is, Sing(1) = Q. Davenport and Schmidt [20] in the 1970s showed that Sing(d) is a set of d-dimensional Lebesgue measure zero. Recently, Cheung and Chevallier [16], building on the spectacular d = 2 work of Cheung [15], have shown that Sing(d) has Hausdorff dimensiond 2 /(d + 1). † The stabiliser Gp = {g ∈ G : g(p) = p} of a parabolic fixed point p is an infinite group that contains a free abelian subgroup of finite index.…”
Section: A Dirichlet-type Theorem and Singular Subsets Of λmentioning
confidence: 99%